2009
DOI: 10.1038/nm.1930
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive in vivo imaging of T cells using a membrane-bound Gaussia princeps luciferase

Abstract: We developed a novel approach to bioluminescent T cell imaging (BLI) using a membrane-anchored form of the Gaussia luciferase (GLuc) enzyme, termed extGLuc, which we could stably express in both mouse and human primary T cells. In vitro, extGLuc+ cells emitted significantly higher bioluminescent signal when compared to cells expressing GLuc, Renilla luciferase (RLuc), and membrane-anchored RLuc (extRLuc). In vivo, mouse extGLuc+ T cells exhibited higher bioluminescent signal when compared to GLuc+ and RLuc+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 34 publications
3
114
1
Order By: Relevance
“…ExtGLuc was retrieved from the rPLSI1180-ExtGLuc-IRES-hr-green fluorescent protein (GFP) vector (kindly provided by the Brentjens Laboratory 29 ) by EcoRI/StuI (blunt), and ligated into EcoRI/SalI (blunt) sites of the third generation lentivector CD711B_1_pCDH_MSCV. Lentiviral particles were produced by transient transfection in 293T cells using pVSV, pREV, and pMDL-PRRE helper plasmids.…”
Section: Lentiviral and Retroviral Transductionsmentioning
confidence: 99%
“…ExtGLuc was retrieved from the rPLSI1180-ExtGLuc-IRES-hr-green fluorescent protein (GFP) vector (kindly provided by the Brentjens Laboratory 29 ) by EcoRI/StuI (blunt), and ligated into EcoRI/SalI (blunt) sites of the third generation lentivector CD711B_1_pCDH_MSCV. Lentiviral particles were produced by transient transfection in 293T cells using pVSV, pREV, and pMDL-PRRE helper plasmids.…”
Section: Lentiviral and Retroviral Transductionsmentioning
confidence: 99%
“…More recently, mouse models demonstrated the efficacy of gene-modified T cells targeting B cell malignancies through chimeric Ag receptors (CARs). Murine and human T cells expressing CAR consisting of an Ab-type recognition domain (scFv) giving CD19 specificity linked to the CD3z signaling molecule have been shown to eradicate established human CD19 + lymphoma when given in conjunction with lymphodepleting conditioning regimens or to immunodeficient mice (3)(4)(5)(6)(7). These receptors are now in earlystage phase I clinical trials at several sites worldwide.…”
mentioning
confidence: 99%
“…However, the secreting nature of the native GLuc enzyme significantly attenuates the in vivo bioluminescent signal from the cell expressing GLuc [44]. Elmer et al [45] reported that this limitation could be overcome by modified Gluc by addition of a CD8 transmembrane domain, and also they produced the membraneanchored form of GLuc-positive cells from both mouse and human primary T cells and demonstrated that the cells have a markedly superior in vivo BLI signal when compared with native GLuc positive T cells.…”
Section: Gaussia Luciferasementioning
confidence: 99%